Positive psychology in a pandemic: buffering, bolstering, and building mental health. Issue 3 (4th May 2022) - Waters, Lea; Algoe, Sara B.; Dutton, Jane; Emmons, Robert; Fredrickson, Barbara L.; Heaphy, Emily; Moskowitz, Judith T.; Neff, Kristin; Niemiec, Ryan; Pury, Cynthia; Steger, Michael
ABSTRACT: As the COVID-19 global health disaster continues to unfold across the world, calls have been made to address the associated mental illness public crisis. The current paper seeks to broaden these calls by considering the role that positive psychology factors can play in buffering against mental illness, bolstering mental health during COVID-19 and building positive processes and capacities that may help to strengthen future mental health. The paper explores evidence and applications from nine topics in positive psychology that support people through a pandemic: meaning, coping, self-compassion, courage, gratitude, character strengths, positive emotions, positive interpersonal processes and high-quality connections. In times of intense crisis, such as COVID-19, it is understandable that research is heavily directed towards addressing the ways in which people are wounded and weakened. However, this need not come at the expense of also investigating the ways in which people are sustained and strengthened.